Bulgaria : Report on the Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report on the Observance of Standards and Codes on Fiscal Transparency on Bulgaria explains a detailed description of practice. Important areas where Bulgaria meets the code include the consistent use of the consolidated general government as the basis for fiscal policy and reporting; and clear articulation of fiscal targets and rules. The capacity of the Minister of Finance, under the terms of the current organic budget law, to authorize additional discretionary spending in the event of revenue overperformance, is problematic because it reduces fiscal transparency and also accountability to the parliament.